Polymersomes with Red/Near‐Infrared Emission and Reactive Oxygen Species Generation. Issue 4 (28th October 2022) - Zhang, Zhihua; Chen, Hui; Wang, Youchao; Zhang, Nian; Trépout, Sylvain; Tang, Ben Zhong; Gasser, Gilles; Li, Min‐Hui
Abstract: In photodynamic therapy (PDT), the uses of nanoparticles bearing photosensitizers (PSs) can overcome some of the drawbacks of using a PS alone (e.g., poor water solubility and low tumor selectivity). However, numerous nano‐formulations are developed by physical encapsulation of PSs through Van der Waals interactions, which have not only a limited load efficiency but also some in vivo biodistribution problems caused by leakage or burst release. Herein, polymersomes made from an amphiphilic block copolymer, in which a PS with aggregation‐induced emission (AIE‐PS) is covalently attached to its hydrophobic poly(amino acid) block, are reported. These AIE‐PS polymersomes dispersed in aqueous solution have a high AIE‐PS load efficiency (up to 46% as a mass fraction), a hydrodynamic diameter of 86 nm that is suitable for in vivo applications, and an excellent colloidal stability for at least 1 month. They exhibit a red/near‐infrared photoluminescence and ability to generate reactive oxygen species (ROS) under visible light. They are non‐cytotoxic in the dark as tested on Hela cells up to concentration of 100 µm . Benefiting from colloidal stability, AIE property and ROS generation capability, such a family of polymersomes can be great candidates for image‐guided PDT. Abstract : Polymersomes with red/near‐infrared (R/NIR) emission and reactive oxygen species (ROS) generation are constructed from an amphiphilic block copolymer based on PEG and polypeptoid. Thanks to the covalent connection of the photosensitizer with aggregation‐induced emission (AIE‐PS), the polymersomes exhibit high AIE‐PS load efficiency and excellent colloidal stability. Benefiting from R/NIR emission and ROS generation, these polymersomes can be good candidates for image‐guided photodynamic therapy.